2020
DOI: 10.1002/ijc.33309
|View full text |Cite
|
Sign up to set email alerts
|

Mammography features for early markers of aggressive breast cancer subtypes and tumor characteristics: A population‐based cohort study

Abstract: Current breast cancer risk models identify mostly less aggressive tumors, although only women developing fatal breast cancer will greatly benefit from early identification. Here, we evaluated the use of mammography features (microcalcification clusters, computer‐generated Breast Imaging Reporting and Data System [cBIRADS] density and lack of breast density reduction) as early markers of aggressive subtypes and tumor characteristics. Mammograms were retrieved from a population‐based cohort of women that were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…associated with the presence of calcifications and that no associated calcifications are signatures of TNBC (41,42). Tan et al found that women with microcalcification clusters in the affected breast are less likely to have TNBCs than those with luminal A breast cancers (43). Our study also showed that the presence of calcifications is associated with the HER2-enriched subtype.…”
Section: Discussionsupporting
confidence: 69%
“…associated with the presence of calcifications and that no associated calcifications are signatures of TNBC (41,42). Tan et al found that women with microcalcification clusters in the affected breast are less likely to have TNBCs than those with luminal A breast cancers (43). Our study also showed that the presence of calcifications is associated with the HER2-enriched subtype.…”
Section: Discussionsupporting
confidence: 69%
“…These elemental signs of human diseases are frequently detected in pathological tissues as consequence of cell homeostasis deregulation. The most common calcifications found in non-bone tissues are breast microcalcifications (21). Deposits of calcium salts in breast are associated to the presence of lesions, both benign and malignant.…”
Section: Role Of Ptx3 In Ectopic Calcificationsmentioning
confidence: 99%
“…Deposits of calcium salts in breast are associated to the presence of lesions, both benign and malignant. Thus, detection of microcalcifications in breast tissues by imaging analysis, such as echography, Magnetic Resonance Imaging (MRI) or most commonly by mammography, currently represents the main breast cancer screening investigation (21). After the pioneering studies of Morgan et al (22)(23)(24), numerous investigations have been performed about the origin of breast microcalcifications.…”
Section: Role Of Ptx3 In Ectopic Calcificationsmentioning
confidence: 99%
“…High mammographic breast density may partly explain this finding, given that previous research has established an association between dense breasts and a false-positive result, as well as between dense breasts and larger tumor size. 5,34,35 In addition, larger tumors might result from a reluctance to undergo screening after a false-positive result, as we found that the next screening's attendance rate was lower for women with a false-positive result compared with those without one.…”
Section: Discussionmentioning
confidence: 81%